ANALISIS PROMOSI DAN KUALITAS PELAYANAN GOCAR (GOJEK) TERHADAP KEPUASAN KONSUMEN STUDI KASUS PADA MASYARAKAT CENGKARENG JAKARTA BARAT - Iwan; Purwatiningsih; Eneng Iviq Hairo Rahayu (Lembaga Pengembangan Kinerja Dosen, 2022)
PT. Gojek has many types of online transportation services, one of which is Gocar. This study aims to determine the effect of promotion and service quality on the formation of consumer satisfaction using Gocar in the Cengkareng area of ​​West Jakarta. The analytical method used is descriptive analysis and multiple linear regression analysis. The number of samples taken is 100 respondents, the sampling technique uses non-probability sampling, with purposive sampling technique, which is a sampling technique where elements of the population are selected with the researcher's considerations and using a Likert scale method questionnaire, to obtain data, the population used is all the people of Cengkareng Jakarta. westerners who have used Gocar online motorcycle taxis. The results of the multiple regression analysis showed that there was a positive and significant influence between the promotion and service quality variables on the formation of customer satisfaction. The results of the t test, the most dominant variable influencing in shaping consumer satisfaction is the quality of service of 0.698